(untitled) (LACCEI, 2024)
Workers are a fundamental part in the development and growth of organizations since their operation and productivity depend on them. Therefore, one of the factors to consider is the job performance and staff turnover of a company for better growth. The objective of the research was to determine the relationship between staff turnover and job performance of janitors and cleaning workers in a SME (Small and Medium-Sized Enterprise). The methodology had a quantitative approach, with a non-experimental design, cross-sectional and correlational level. The sample consisted of 120 workers, including janitors and cleaning workers to whom a survey was applied to collect information. The results obtained showed a value p0.05 therefore, the null hypothesis is rejected what’s more, a moderate positive correlation (r = 0.359) was determined between staff turnover and job performance likewise, a moderate positive correlation (r = 0.380) between voluntary turnover and job performance finally, a moderate positive correlation (r = 0.352) between involuntary turnover and job performance. It was concluded that there is a relationship between staff turnover and job performance of janitors and cleaning workers in the MSE company.